Kick it like Özil? Decomposing the native-migrant education gap - Annabelle Krause; Ulf Rinne; Simone Schüller (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
We investigate second generation migrants and native children at several stages in the German education system to analyze the determinants of the persistent native-migrant gap. One part of the gap can be attributed to differences in socioeconomic background and another part remains unexplained. Faced with this decomposition problem, we apply linear and matching decomposition methods. Accounting for differences in socioeconomic background, we find that migrant pupils are just as likely to receive recommendations for or to enroll at any secondary school type as native children. Comparable natives, in terms of family background, thus face similar difficulties as migrant children. Our results point at more general inequalities in secondary schooling in Germany which are not migrant-specific.
Keywords: J15; J24; I21; 330; migration; education; human capital; Germany; tracking